2020
DOI: 10.1038/s41598-020-72418-4
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral sequence reconstruction produces thermally stable enzymes with mesophilic enzyme-like catalytic properties

Abstract: Enzymes have high catalytic efficiency and low environmental impact, and are therefore potentially useful tools for various industrial processes. Crucially, however, natural enzymes do not always have the properties required for specific processes. It may be necessary, therefore, to design, engineer, and evolve enzymes with properties that are not found in natural enzymes. In particular, the creation of enzymes that are thermally stable and catalytically active at low temperature is desirable for processes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 84 publications
1
42
0
Order By: Relevance
“…Thus, use of ASR pointed to progenotes that were even more thermophilic than the Archaea , consistent with the high heat of the primordial environment. Similar studies with many other enzymes have further confirmed the conclusion that early organisms were indeed endowed with superior thermoresistance, adding confidence to ASR [ 50 , 59 , 60 , 61 , 62 , 63 ]. To the molecular biologist, the ASR studies provide an opportunity to understand the roles of specific amino acids in thermophilia; however, this requires analyses of additional proteins and determination of their structures.…”
Section: Rationale Of Choice Of Heat-relevant Organisms and Macromsupporting
confidence: 66%
“…Thus, use of ASR pointed to progenotes that were even more thermophilic than the Archaea , consistent with the high heat of the primordial environment. Similar studies with many other enzymes have further confirmed the conclusion that early organisms were indeed endowed with superior thermoresistance, adding confidence to ASR [ 50 , 59 , 60 , 61 , 62 , 63 ]. To the molecular biologist, the ASR studies provide an opportunity to understand the roles of specific amino acids in thermophilia; however, this requires analyses of additional proteins and determination of their structures.…”
Section: Rationale Of Choice Of Heat-relevant Organisms and Macromsupporting
confidence: 66%
“…To this effect, Furukawa et al have identified an ancestor of 3-isopropylmalate dehydrogenase (IPMDH), a key enzyme in the biosynthesis of leucine, which offers improvements in its stability and activity over extant IPMDH enzymes from present-day organisms through construction and analysis of a phylogenetic tree. 72 Following inference and identification of two ancestral protein sequences, dubbed ancIPMDH-IQ and ancIPMDH-ML, the group successfully expressed each protein in E. coli and, after isolating the enzymes for further investigation, discovered they provided increased thermal stability and improved catalytic activity at low temperatures compared to their modern homologues. 72 This work demonstrates just one of many potential uses for ancestral protein reconstruction, as other reports describe how ancestral proteins might possess higher degrees of substrate promiscuity compared to their modern offspring, thus offering potentially valuable characteristics to organic chemists seeking diverse and novel bond-forming activity.…”
Section: Accessibility Of Biocatalysis To Synthetic Chemistsmentioning
confidence: 99%
“…Here, ASR is a sequence-based protein redesign method which can generate ancestral proteins located at each node of the phylogenetic tree (20,21). Ancestral proteins often have desirable properties for use in practical applications, such as high thermostability (22,23) and broad substrate selectivity (24). Therefore, ASR is currently being adopted as a tool for protein engineering (25).…”
Section: Introductionmentioning
confidence: 99%